Proteome profiling reveals immune responses in Japanese flounder (Paralichthys olivaceus) infected with Edwardsiella tarda by iTRAQ analysis. Issue 66 (July 2017) - Wang, Lei; Shao, Changwei; Xu, Wenteng; Zhou, Qian; Wang, Na; Chen, Songlin
Abstract: The liver is an important organ for bacterial pathogen attack in fish. The differential proteomic response of the Japanese flounder liver to Edwardsiella tarda infection was examined using isobaric tags for relative and absolute quantitation (iTRAQ) labeling followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). A total of 3290 proteins were identified and classified into categories related to biological process (51.4%), molecular function (63.6%), and cellular component (57.7%). KEGG enrichment analysis indicated the complement and coagulation cascade pathways and the mineral absorption pathway were significantly enriched. Among the differentially expressed proteins, those involved in mediating complement cascade (e.g. complement component C7, C8, C9, complement factor H, complement factor Bf/C2) and mineral absorption (e.g. ferritin, STEAP-4) were most significantly upregulated during infection. Subsequently, five significantly upregulated (C4, C8beta, ferritin middle subunit, PRDX4-like and KRT18) and one significantly downregulated (transferrin) candidate immune proteins were validated by multiple reaction monitoring (MRM) assays. Furthermore, changes in expression of 15 proteins in the complement cascade and mineral absorption pathways were validated at the transcriptional level using quantitative real-time PCR (qPCR). The transcriptional levels of four transcription factors (p21Ras, Rab-31-like, NF-κB, STAT3) were also investigated by qPCR following infection with E. tarda . This study contributes to understanding the defense mechanisms of the liver in fish. Highlights: The study identified the differently expressed liver proteins and two signal pathways of Japanese flounder under E. tarda infection by iTRAQ. Transcriptomic profiles analysis of fifteen proteins in complement cascade and mineral absorption were investigated. mRNA levels of four transcription factors confirmed the upregulated of RNA/DNA ratio in E. tarda infection.